Discovery and vertical transmission analysis of Dabieshan Tick Virus in Haemaphysalis longicornis ticks from Chengde, China - Xu, Xiaofeng; Gao, Zhihua; Wu, Youhong; Yin, Hong; Ren, Qiaoyun; Zhang, Jie; Liu, Yongsheng; Yang, Shunli; Bayasgalan, Chimedtseren; Tserendorj, Ariunaa; Yang, Xiaolong; Chen, Ze (Frontiers in Microbiology, 2024)
Introduction Ticks are important blood-sucking ectoparasites that can transmit various pathogens, posing significant threats to the wellbeing of humans and livestock. Dabieshan tick virus (DBTV) was initially discovered in 2015 in Haemaphysalis longicornis ticks from the Dabieshan mountain region in Hubei Province, China. In recent years, DBTV has been discovered in various regions of China, including Shandong, Zhejiang, Liaoning, Hubei, Yunnan, and Guizhou Provinces. However, the researches on tick-borne transmission of DBTV are scarce. Methods This study utilized the small RNA sequencing (sRNA-seq) method to identify tick-associated viruses in ticks collected from Chengde in Hebei Province and Yongcheng in Henan Province, leading to the discovery of a new DBTV strain in Hebei. The complete coding genome of DBTV Hebei strain was obtained through RNA-seq and Sanger sequencing. Furthermore, the transmission experiment of DBTV in H. longicornis was examined in laboratory for the first time. Results DBTV was detected in newly molted adult H. longicornis ticks collected in Chengde, Hebei Province. Additionally, DBTV was also detected in both unfed nymphs and engorged females of H. longicornis collected from Chengde, with a positive rate of 20% and 56.25%, respectively. The complete coding genome of DBTV (OP682840 and OP716696) were obtained, and phylogenetic analysis revealed that the DBTV Hebei strain clustered with previously reported DBTV strains. Furthermore, this virus was observed in engorged females, eggs, and larvae of the subsequent generation. Discussion It is necessary to expand the scope of DBTV investigation, particularly in northern China. This study demonstrated that DBTV can be transmitted from engorged females to larvae of the next generation. Moreover, the detection of DBTV in unfed nymphs and adults (which moulted from engorged nymphs) collected from the filed of Chengde suggests that H. longicornis serves as a potential transmission host and reservoir for DBTV through transstadial and transovarial transmission. However, there remains a lack of research on the isolation and pathogenicity of DBTV, highlighting the need for further studies to mitigate potential harm to the health of animals and humans.